Can FinTech improve corporate environmental, social, and governance performance?—A study based on the dual path of internal financing constraints and external fiscal incentives - Du, Pengcheng; Huang, Shijun; Hong, Yu; Wu, Woran (Frontiers in Environmental Science, 2022)
The environmental, social and governance (ESG) concept has become a global concern, and the fulfillment of corporate ESG responsibility is a crucial link to the achievement of China's "double carbon goal" and the sustainable development of the whole society. Can financial technology (FinTech) "empower" traditional financial institutions with technology to improve corporate ESG performance? Based on this, this paper examines the relationship between regional FinTech development and corporate ESG performance and its underlying mechanisms from internal and external perspectives, using data from Chinese A-share listed companies from 2011 to 2020. The following were found: (1) The level of regional FinTech development significantly contributes to firms' ESG performance, and the results remain robust after mitigating endogeneity using Bartik instrumental variables and difference-in-differences model estimation. (2) Mechanistic analysis finds that FinTech not only alleviates the internal financing constraints of firms, but also enhances the external government subsidies and tax rebates of firms. These significantly contribute to the improvement of firms' ESG performance. (3) Heterogeneity analysis shows that the contribution of FinTech to improving corporate ESG performance is more pronounced in the eastern region, mature firms and firms with CEOs with unbanked financial backgrounds. Therefore, in the context of sustainable development, we should continue to promote the development of FinTech, use modern technology to "empower" finance, and help enterprises balance economic and social benefits to build a sustainable country.